An Experimental Investigation of Compaction-Induced Breakage and Ultimate State for Rock Granular Materials - Hailing Kong; Xinyu Miao; Chengzhen Zuo; Kongyu Hu; Luzhen Wang (Advances in Civil Engineering)
Rock granular materials are among the most common solid filling materials, and their mechanical behavior depends on their grading, which changes due to breakage during loading and compaction. This study conducted compaction experiments on rock granular materials to investigate compaction characteristics, grain size distribution (GSD) evolution, breakage, and fractal behavior and to explore the ultimate breakage state during the compaction process. Although the breakage index theoretically suggested the existence of a crushing limit, experimental results did not confirm this. In this paper, the fractal dimension was used as an effective approach to explore the crushing limit and ultimate distribution of rock granular materials. The fractal dimension ranged from 2.33 to 2.55 for single-size samples and from 2.60 to 2.78 for mixed samples, as determined through mathematical calculations. Understanding the crushing limit of granular materials can assist engineers in designing optimal filling ratios and allowable compaction levels for solid material filling applications.